Prospecção tecnológica do jaborandi (Pilocarpus microphyllus) : espécie economicamente importante no norte e nordeste do Brasil - Lima, David Fernandes (2015)
The Pilocarpus microphyllus Stapf ex Wardlew spe cie is a native plant from north and northeast of Brazil occurring in eastern of Pará state, n orthwest and north of Maranhão and Piauí. It is one of the most important Brazilian medicinal species presents in pharmacopoeia of the entire world due to the use of its active pilocarpine. When using the Web of Science periodic base with Pilocarpus genus the result was 56 articles and for the specie Pilocarpus microphyllus the result found was 17 articles . The search for patents was using the basic patent Derwent Innovation Index, INPI, EPO and USPTO getting a contrasting result with the number of articles, recital Japan highlighted in protection of research involving Pilocarpus. The genus Pilocarpus with emphasis on Pilocarpus microphyllus specie through published articles and patents granted in Brazil and in other countries highlights the economic and industrial importance of the specie and provides future perspectives in the discovery of new pharmacological and biotechnological applications of the others alkaloid s which so far remains unknown.